Assessment of the Centralization of Root Canal Preparation with Rotary Systems - Daniela Siqueira Lopes; Mariana Albuquerque Veiga Pessoa; Andréa Cruz Câmara; Carlos Menezes Aguiar (University of Zagreb. School of Dental Medicine, 2016)
Objective: Apical deviations are important factors in endodontic therapy, since they can cause the treatment failure. The aim of the present study was to determine the centering capacity of ProTaper Universal™, Twisted File™ and Revo-S® rotary systems using cone beam computed tomography analysis before and after the instrumentation of root canals. Materials and Methods: Thirty mesiobuccal roots from human lower first molars were divided into three groups of ten: Group 1 - ProTaper Universal™ Rotary System; Group 2 - Twisted File™ Rotary System; and Group 3 - Revo-S® Rotary System. All teeth were scanned using computed tomography to determine the condition of the root canal before and after instrumentation (4mm, 3mm and 2mm from the root apex). Images were made using ICAT VISION software for both instrumented and non-instrumented canals. Results: The results were analyzed statistically using the Kolmogorov-Smirnov normality test for quantitative variables. Comparisons were made with two groups (Mann-Whitney - abnormal) and with more than two groups (Kruskal Wallis - abnormal). The level of significance was set at p<0.05. A statistically significant difference was found for the measurement of 4 mm between the "ProTaper Universal" and "Twisted File" systems. For the Twisted File system, a statistically significant difference was recorded between the measurements of 4mm and 3 mm. Conclusion: None of the assessed instruments was completely effective in terms of the biomechanical preparation of root canals since all created deviation from the original anatomy of the canal.